Are law students’ individual differences in the post-pandemic world related to performance? - Pilotti, Maura A. E.; Hassan, Samia A. M.; El Alaoui, Khadija; Aldossary, Farah (Frontiers in Education, 2023)
The present study examined the dispositions of female undergraduate law students one semester after their return to face-to-face classes. It aimed to determine the contribution of particular dispositions to academic performance. Dispositions selected were those that are known to promote adaptation, such as self-efficacy and emotional intelligence, as well as resistance-to-change attitudes, which are known to do the opposite. Freshmen (n = 261) and seniors (n = 236) were included to assess whether dispositions varied with the length of students’ academic experience. Participants were students from a society in which females’ academic success is seen as key to advancing a sustainable, competitive, and gender-equitable economy. Thus, at the time of the study, these students were expected to quickly readjust to the post-pandemic world of face-to-face instruction. Participants completed questionnaires on the selected dispositions. Academic performance was operationalized as the grade point average obtained in the semester following a return to face-to-face classes. In the study, the length of academic experience mattered. Seniors exhibited greater self-efficacy and emotional intelligence. For both groups, performance increased with emotional reactions to forced change, thereby suggesting that noticing environmental changes that challenge one’s sense of agency is beneficial. However, in seniors, performance decreased with their short-term focus, whereas in freshmen, it increased with emotional intelligence, indicating that college experience shapes the utility of particular traits.